2022
DOI: 10.53855/bjt.v25i4.481_in
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinical and Psychosocial Factors on the Acceptance of no Human Organs in Transplants: Xenotransplants

Abstract: Introduction: Xenotransplantation is defined as the transplantation of cells, organs and tissues between different species. It is studied as an alternative method to acquire an adequate supply of human organs, which imbalance in demand results in increased mortality on the transplantation waiting list. The aim of the present study was to deepen knowledge about the psychosocial aspects that influence the acceptance or refusal of xenotransplantation, seeking to add information tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, it is important to recognize that the consumption of pork is considered a sin in Islam; therefore, adherents of this religion may hold negative views towards pig‐to‐human organ transplantation 17 . Furthermore, psychosocial factors can influence the acceptance of XTx, including attitudes towards organ donation and the risk of zoonotic diseases 18–20 . The potential for cross‐species viral transmission poses a threat to the health of individuals and the wider population and may cause fear of zoonotic diseases 8,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to recognize that the consumption of pork is considered a sin in Islam; therefore, adherents of this religion may hold negative views towards pig‐to‐human organ transplantation 17 . Furthermore, psychosocial factors can influence the acceptance of XTx, including attitudes towards organ donation and the risk of zoonotic diseases 18–20 . The potential for cross‐species viral transmission poses a threat to the health of individuals and the wider population and may cause fear of zoonotic diseases 8,19 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, psychosocial factors can influence the acceptance of XTx, including attitudes towards organ donation and the risk of zoonotic diseases. [18][19][20] The potential for cross-species viral transmission poses a threat to the health of individuals and the wider population and may cause fear of zoonotic diseases. 8,19 In addition, one study found that attitudes towards XTx may be affected by various factors such as age, sex, geographical location, and years of academic education.…”
mentioning
confidence: 99%